Data Mining jako narzędzie controllingu dla małych i średnich przedsiębiorstw - Andracki, Sebastian (Data mining as the controlling instrument in the sector of small and medium-sized enterprises, 2006)
The article discusses the chances and risks of implementation of modem analytical methods and tools (OLAP and Data Mining) to retrieving the huge data archives. Application of new opportunities refers to a concept of management cycle. The problem of data quality in the context of three lever data quality approach is also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 11-19